Audit committees: structure and corporate governance - Guðbjartsson, Einar; Jónsson, Eyþór Ívar; Snorrason, Jón Snorri (Research in applied business and economics, 2018)
The aim of this paper is to report partial results related to structure of audit committees to achieve effectiveness, the composition. Three dimensions are viewed; diversity, expertise and independence of audit committees board members. Comparison of two studies, one from 2012 and the other from 2016. The paper identifies, among other things, board members age, education and the election of members. In the Annual Accounts Act, no. 3/2006, it is required for certain legal entities, public interest entities, to establish an audit committee. The purpose of the audit committee is to ensure the high quality and high reliability of financial reporting and financial information. It does not matter whether the reports are for use of the administrators of the entity or for the stakeholders outside the entity. The structure of the audit committees can be decisive weather the aim of the law will be fulfilled or not. The board constitutionals the audit committee. The audit committee must supervise the board´s actions within the frame of the Annual Accounts Act. The paper is to seek for if the audit committee´s structure can affect the effectiveness and how it fits in with corporate governance. To accomplish that, three hypotheses are stated: 1) Structure of audit committee’s is diversity, 2) board members have relevant expertise knowledge and 3) the majority of the audit committee are independent from the entity. The survey is done among the leading companies and institutions of Iceland (which fall within the definition of “public interest entities”). This is the first study of its kind, specifically focusing on audit committees. Tilgangur greinarinnar er að skoða samsetningu endurskoðunarnefnda m.t.t. markvirkni. Áhersla er lögð á að skoða fjölbreytni, sérfræðiþekkingu og óhæði nefndarmanna. Engar rannsóknir hafa verið gerðar á endurskoðunarnefndum á Íslandi sem miða að því að skoða þætti eins og samsetningu nefnda m.t.t. markvirkni endurskoðunarnefnda. Þar af leiðandi voru þrjár tilgátur settar fram til þess að meta ...